Inhibition by components of Glycyrrhiza uralensis of 3CLpro and HCoV-OC43 proliferation - Jang Hoon Kim; Yea-In Park; Mok Hur; Woo Tae Park; Youn-Ho Moon; Yun-Chan Huh; Tae IL Kim; Min Hye Kang; Jong Seong Kang; Chong Woon Cho; Junsoo Park (Taylor & Francis Group, 2023)
Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). 3CLpro is a key enzyme in coronavirus proliferation and a treatment target for COVID-19. In vitro and in silico, compounds 1-3 from Glycyrrhiza uralensis had inhibitory activity and binding affinity for 3CLpro. These compounds decreased HCoV-OC43 cytotoxicity in RD cells. Moreover, they inhibited viral growth by reducing the amounts of the necessary proteins (M, N, and RDRP). Therefore, compounds 1-3 are inhibitors of 3CLpro and HCoV-OC43 proliferation.